A contribution to the development of "soft skills" in Industrial Engineering: Experience in Numerical Analysis and Advanced Calculus (AACINI - International Journal of Industrial Engineering, 2024)
Qualities such as creativity, originality, social and emotional intelligence are key to the professions of the future. Academic training in engineering careers must go far beyond technological training, it must also include skills related to efficient communication and teamwork, among others.In the Numerical Analysis and Advanced Calculus course, included in the third level of the Industrial Engineering curriculum of Facultad Regional San Nicolás, UTN, considering the graduation skills in engineering careers proposed by the CONFEDI (Federal Council of Deans of Engineering) the development of some soft skills was added to the specific contents of the subject. In particular, the development of activities related to verbal and written communication.In 2022 an experience was carried out where students were proposed a practical group work where they had to choose an engineering problem, preferably related to the career, to be solved with the numerical techniques learned in the subject. Then, they had to make an oral presentation describing the resolution process carried out and showing the advantages and disadvantages of the applied methods. The aim of this work is to present the experience carried out, results obtained, and the opinion of the students about carrying out this type of activities in "hard subjects" of the career.
Keywords: graduation competencies; soft skills; oral communication; problem resolution; assessment